Pengaruh Penerapan Anggaran Berbasis Kinerja Terhadap Akuntanbilitas Publik pada Instansi Pemerintah - Zachari Abdallah; Cyntia Carolina (LPPM - STIE SAKTI ALAM KERINCI, 2018)
This study aims to determine the effect of the application of performance-based budgeting to the public Accountability of government agencies at the Department of Public Works cultivated fields river town full clan . Sampling technique using sample becomes saturated criteria are all employees of the public works in the field of coaching clan as well as all the activities in performance-based budgeting . Number of questionnaires distributed as many as 32 pieces and all can be processed using simple linear regression analysis , the determinant coefficient , and t test and using SPSS 22.0. The results showed that the application of performance-based budgeting and significant positive effect on public Accountability in government agencies .